Level of anxiety and factors influencing anxiety among orthopedic surgical patients in a secondary care center in India - T Jeni Christal Vimala; Rajesh Martin; Anbu Suresh Rao; Melvin Joy (Wolters Kluwer Medknow Publications, 2021)
Background: The purpose of the present study aimed to assess the level of anxiety and factors influencing anxiety among orthopedic surgical patients admitted to a secondary care center in India. Methods: The study was conducted for a period of 3 months. A quantitative approach with a descriptive design was used. Simple random sampling was used to select 46 orthopedic inpatients. Demographic and clinical data were collected using a self-developed pro forma. State-Trait Anxiety Inventory form Y-1 was used to assess anxiety, and factors influencing anxiety were assessed by a self-developed questionnaire. Results: Out of 46 participants, 60.90% have low anxiety, 15.20% have moderate, and 23.90% have severe anxiety. Regarding factors influencing anxiety, 78.30% have fear about postoperative pain; 60.90% have fear about surgery; 58.70% have fear about anesthesia, the outcome of surgery, and economic issues; and 52.20% have fear of dependency and postponement of surgery. Some other factors are fear of complications and lack of sleep during night 45.70%, fear about family issues 37%, fear of postoperative nausea 34.80%, fear of death 23.90%, fear about the structure of the ward 17.40%, and fear due to lack of preoperative instructions 13%. Conclusions: Anxiety is common among patients waiting for orthopedic surgery. It is important to identify the factors influencing anxiety as a routine nursing care to reduce anxiety level.